The relationship between vitamin D and obesity. (June 2014) - Soskić, Sanja; Stokić, Edita; Isenović, Esma R.
Abstract Currently, vitamin D deficiency and obesity are pandemic diseases and they are associated with cardiovascular (CV) disease, metabolic syndrome and type 2 diabetes mellitus (T2DM) and other diseases. Concentrations of 25-hydroxyvitamin D (25(OH)D) (25D) are considered as the best indicator of total body vitamin D stores. An association between reduced circulating 25D concentrations and obesity is well known, but the mechanisms are not totally clear. The role of vitamin D supplementation is still uncertain and prospective interventions will establish its influence, if any, in the treatment of obesity. Vitamin D deficiency is associated with the presence of a cardiometabolic risk profile in the obese. Future trials may establish a role for Vitamin D supplementation in individuals at increased CV risk.